Answer:
y=5x-15
Step-by-step explanation:
Differentiate the given solution:
![y=\dfrac1{x^2+C}\implies y'=-\dfrac{2x}{(x^2+C)^2}](https://tex.z-dn.net/?f=y%3D%5Cdfrac1%7Bx%5E2%2BC%7D%5Cimplies%20y%27%3D-%5Cdfrac%7B2x%7D%7B%28x%5E2%2BC%29%5E2%7D)
Substitute
and
into the ODE:
![-\dfrac{2x}{(x^2+C)^2}+2x\left(\dfrac1{x^2+C}\right)^2=0](https://tex.z-dn.net/?f=-%5Cdfrac%7B2x%7D%7B%28x%5E2%2BC%29%5E2%7D%2B2x%5Cleft%28%5Cdfrac1%7Bx%5E2%2BC%7D%5Cright%29%5E2%3D0)
and it's easy to see the left side indeed reduces to 0.
Answer:
90 + 0.1 + 0.02 + 0.005
Step-by-step explanation:
Well this only simplifies to a smaller equation
so the answer would be...
2a²-9b²
Answer:
equilateral: E
scalene: F
isosceles: G
Step-by-step explanation:
equilateral = all sides are equal
scalene = no sides are equal
isosceles = two sides are equal